SISTEM INFORMASI KREDIT SAHABAT PADA BADAN USAHA MILIK DESA (BUMDES) DESA SEMAMUNG BERBASIS WEB - Rodianto; Jundi Khoirullah; Yana Karisma (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
One of the efforts the acceleration of the economy of the village is the availability of venture capital. Each village has a business entity that is named the village owned enterprises (BUMDes). A business entity has one work program, namely